Molecular mechanisms of anti-inflammatory activity mediated by flavonoids - Gomes, Ana (2015)
Flavonoids (or bioflavonoids) are naturally occurring compounds, ubiquitous in all vascular plants. These compounds have been considered to possess anti-inflammatory properties, both in vitro and in vivo. Although not fully understood, these health-promoting effects have been mainly related to their interactions with several key enzymes, signaling cascades involving cytokines and regulatory transcription factors, and antioxidant systems. The biological effects of flavonoids will depend not only on these pharmacodynamic features but also on their pharmacokinetics, which are dependent on their chemical structure, administered dose schedule and route of administration. Thus, the therapeutic outcome mediated by flavonoids will result from a complex and interactive network of effects, whose prediction require a deep and integrated knowledge of those pharmacokinetic and pharmacodynamic factors. The aim of the present review is thus to provide an integrated update on the bioavailability and biotransformation of flavonoids and the mechanisms of activity at the molecular, cellular, organ and organism levels that may contribute to their anti-inflammatory effects.